The mediating role of employee commitment on the impact of human resource management practices and transformational leadership style on employee performance - Mahfouz, Shatha Suleiman Atieh Abu
Improving the performance of the employees in the construction sectors in Jordan is extremely important since the industry contributes significantly to the country's economy. Every year, huge development fund is spent on the industry since it triggers other economic activities. However, the sector itself is still confronted with issues concerning lack of qualified workforce, human resource practices, leadership, employee commitment, and employee performance that slow down economic growth. As a result, many projects are being suspended and there are even occurrences of work closure. Consequently, the research was aimed at investigating the mediating effect of employee commitment on the impact of HRM practices and transformational leadership style on employee performance of building construction companies in Jordan. A survey research design that incorporated quantitative method and cross sectional study of the employees of construction companies was employed to test the hypothesised relationship among the constructs. The sampling frame of the target population was not available and staff directory was not available. Hence, the researcher had to develop a surrogate sampling frame by distributing self-administered questionnaires to the respondents and draw a random sample from the surrogate sampling frame. Consequently, 1000 usable questionnaires were returned to be used as surrogate sampling frame. Using simple random sampling method, a total of 300 respondents were selected randomly. Data were analysed using Structural Equation Modelling (SEM) technique through lBM-SPSS-AMOS version 24.0 software. HRM practices were found to have a significant effect on employee performance and employee commitment. Transformational leadership had significant indirect irnpact on employee performance. Employee commitment had significant direct Impact on employee performance. Employee ommitment acted as a partial mediator of the relationship between HRM practices and employee performance. Employee commitment also fully mediated the relationship between transformational leadership and employee performance. The novelty of the research was the construction of an inductive model, called the Employee-Directed Transformational Leadership Model (EDTLM), which theoretically implied relationships among transformational leadership, human resource practices, employee commitment, and employee performance. The research had proven that employee commitment was one of the influencers of employee performance. It partially mediated the relationship between human resource practice and employee performance and fully mediated the relationship between transformational leadership and employee performance. The other influencers were human resource practice and transformational leadership. The findings could be used to guide the management team of building construction companies in Jordan to focus on the interrelationships among EDTLM constructs, their variables, and values to improve employee performance. The government and policy makers alike should utilize the research outcomes to spur the economic development of the country.